2014
DOI: 10.1590/s1677-5538.ibju.2014.05.18
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Penile Length in Patients Undergoing Partial Penectomy for Penile Cancer: Novel Application of the Ventral Phalloplasty Oncoplastic Technique

Abstract: _______________________________________________________________________________________The ventral phalloplasty (VP) has been well described in modern day penile prosthesis surgery. The main objectives of this maneuver are to increase perceived length and patient satisfaction and to counteract the natural 1-2 cm average loss in length when performing implantation of an inflatable penile prosthesis. Similarly, this video represents a new adaptation for partial penectomy patients. One can only hope that the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…[37][38][39][40] Also there are some techniques used for penile lengthening such as suspensory ligament release, augmentation corporoplasty, ventral phalloplasty, and suprapubic lipectomy, monsplasty. [41] Ventral phalloplasty would be used for penile lengthening with or after partial penectomy as Wallen et al [42] reported good results. Aphallia is a rare congenital defect with the ratio of 1/30 million births.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40] Also there are some techniques used for penile lengthening such as suspensory ligament release, augmentation corporoplasty, ventral phalloplasty, and suprapubic lipectomy, monsplasty. [41] Ventral phalloplasty would be used for penile lengthening with or after partial penectomy as Wallen et al [42] reported good results. Aphallia is a rare congenital defect with the ratio of 1/30 million births.…”
Section: Discussionmentioning
confidence: 99%
“…The penile stump can then be anchored to the pubic bone to prevent retraction [79]. While initially used to increase perceived penile length in patients undergoing penile implants, Wallen et al [80] incorporated the ventral phalloplasty technique after partial penectomy. A transverse 'V'-shaped excision at the penoscrotal junction is made and the wound is then closed in a longitudinal fashion to improve penile cosmesis.…”
Section: Adjunctive Surgical Maneuvers For Improving Penile Cosmesis mentioning
confidence: 99%
“…One documented means of improved functional outcomes comes from literature by Wallen et al in describing the ventral phalloplasty for optimizing penile length following partial penectomy. The average loss of 1–2 cm following partial penectomy causes significant emotional distress in patients and may be minimized by performing a ventral phalloplasty in patients undergoing surgical resection ( 78 ). The procedure offers a simple adaptation that can add to patient satisfaction and be performed at that time of the original cancer operation.…”
Section: Reconstructive Modalitiesmentioning
confidence: 99%